Proteomic Investigations of Adaptations to Exercise in Humans - Thomas, Aaron (My University, 2024)
The mechanisms leading to a hypertrophic versus an endurance phenotype, the hallmarks of resistance exercise (RE) or aerobic exercise (AE), respectively, are still largely unknown. In humans, exposure of exercise naïve persons to either AE or RE results in their skeletal muscle exhibiting generic ‘exercise stress-related’ signalling, transcription, and translation responses. However, with increasing engagement in AE or RE, the responses become refined, and the phenotype typically associated with each form of exercise emerges. Phosphorylation of specific residue sites has been a dominant focus, with canonical signalling pathways (i.e. AMPK and mTOR) studied extensively in the context of AE and RE, respectively. These alone, along with protein synthesis, have only begun to elucidate key differences in AE and RE signalling. Still, key yet uncharacterized differences exist in signalling and regulation of protein synthesis that drive unique adaptation to AE and RE. Omic studies are required help in understanding the mechanisms that lead to the divergent relationship between exercise and phenotypic outcomes of training. In study 1 of this thesis, 16 young, healthy subjects (n=4 pilot study and n=12 follow-up study; 6 males [M] and 6 females [F]) performed a unilateral session of AE or RE with biopsies taken before (Pre), immediately post (0h) and 3 hours (3h) following recovery. Muscle tissue (cohort 1: n=4) was subjected to deep phosphoproteomic analyses, identifying nearly 13000 individual phosphosites and unique clusters specifically associated with AE and RE. Follow-up studies (cohort 2: n=12) were performed, and the outcomes support a thesis that prolonged activation of the MKK3/6, p38, and MK2 signalling axis is a resistance exercise-specific phenomenon and is critical in the process of muscle hypertrophy. We also demonstrated that the activation of signalling through MKK3 is robustly correlated with the increase in myofibrillar protein synthesis that occurs after RE in humans (r2= 0.60, p<0.01). In study 2, we sought to determine the divergent changes in the skeletal muscle proteome induced earlier and later in a training program using both RE and AE, in parallel, in healthy young males and females. We investigated muscle adaptations to AE and RE training during the early untrained versus trained state using novel deuterium oxide labelling and proteomic techniques. A total of 14 (8F/6M) healthy individuals completed 10-wk of thrice weekly unilateral resistance and unilateral aerobic training. Our data illustrated the common and unique networks of protein regulation following AE and RE. Specifically we highlighted the influence that both AE and RE have on mitochondrial proteins, likely aimed at improving metabolic function and possibly underpinning an increase in oxidative capacity and in supporting tissue protein remodelling. In both AE and RE, we identified changes in protein abundance that did not align with individual protein synthetic rates, suggesting that targeted degradation of certain proteins may be an adaptive feature of the shared response to aerobic and resistance training. To date, this work represents the most in-depth analysis of protein-specific fractional synthesis rates in human muscle in vivo in response to differential forms of exercise training. Together, these studies generate novel insights into training mode-specific muscle adaptations by measuring widespread phosphorylation and protein-specific changes in combination with individual protein synthesis rates.
PROTEOMIC INVESTIGATIONS OF ADAPTATIONS IN SKELETAL MUSCLE TO AEROBIC AND RESISTANCE EXERCISE IN HUMANS
Keywords: Muscle; Exercise; Protein